Construyendo identidades de género a través de nombres comerciales en el paisaje lingüístico de la ciudad de Nalchik - Prokudina, Olga A. (Cuadernos de Rusística Española, 2012)
The article deals with the study of an open and constantly enriched sub-system of the Names Proper – commercial names, which are intentionally created lexical units, imposing an artificial link between the target audience and the positioned image. Commercial names are regarded here as complex antroposemiotic configurations with special emphasis on their communicative function, which provides a possibility of specific way of circulation of information resulting in consumption of cultural phenomena and constructing gender identities. An attempt is made to demonstrate how the boarder-lines of the core of the concepts “man” and “woman” reflecting archetypical gender images are extended due to the positioning of female and male images through commercial names.